1998
DOI: 10.1002/(sici)1096-8652(199812)59:4<288::aid-ajh4>3.0.co;2-i
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence of hemophilia in the United States

Abstract: An active surveillance system was used to identify all residents with hemophilia in six U.S. states (Colorado, Georgia, Louisiana, Massachusetts, New York, and Oklahoma). A hemophilia case was defined as a person with physician-diagnosed hemophilia A or B and/or a measured baseline factor VIII or IX activity (FA) of 30% or less. Case-finding methods included patient reports from physicians, clinical laboratories, hospitals, and hemophilia treatment centers. Once identified, trained data abstractors collected c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
3
1

Year Published

2001
2001
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 308 publications
(134 citation statements)
references
References 14 publications
3
127
3
1
Order By: Relevance
“…The system was designed to identify and collect a wide variety of information about all PWH residing in these states [6]. PWH were identified through lists obtained from physicians, clinical laboratories, hospitals, HTCs, and other sources.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The system was designed to identify and collect a wide variety of information about all PWH residing in these states [6]. PWH were identified through lists obtained from physicians, clinical laboratories, hospitals, HTCs, and other sources.…”
Section: Methodsmentioning
confidence: 99%
“…PWH were identified through lists obtained from physicians, clinical laboratories, hospitals, HTCs, and other sources. Demographic, clinical, treatment, and outcome information were collected annually from medical records by trained data abstractors using a standard data collection form previously described [6].…”
Section: Methodsmentioning
confidence: 99%
“…In the United States, incidence of hemophilia (severe, moderate, and mild) was 2 Â 10 À4 among newborn males, with 79% of cases being of hemophilia A [Soucie et al, 1998]. Among these, severe hemophilia A (due to complete or nearcomplete loss of function of F8) constitutes 43%, corresponding to b=6.8 Â 10…”
Section: F8 Hemophilia Amentioning
confidence: 99%
“…In 1992, researchers found that DNA inversion within the X chromosome was responsible for half of the most serious cases of hemophilia A [3]. In 1998, the U.S. population-based estimate of age-adjusted prevalence of hemophilia A was 10.5 cases per 10,000 males, with an overall estimated national population of 13,321 persons with hemophilia A [4].…”
Section: Introductionmentioning
confidence: 99%